ANALISIS KOMPILASI HUKUM ISLAM PASAL 84 TENTANG NUSYUZ ISTRI PERSPEKTIF MAZHAB HANAFI DAN MAZHAB SYAFI’I - rahmat ramadhan rahmat (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2021)
In the Compilation of Islamic Law the issue of nusyuz is regulated in article 84, although there are rules regarding nusyuz in the KHI, there is no definite understanding of the problem of nusyuz, which in article 84 only regulates the issue of nusyuz from the wife's side. As for the meaning of the meaning of nusyuz itself, scholars have different opinions, including the opinion of Imam Shafi'i and Imam Hanafi. This type of research is library research (library research). The approach used is descriptive analytic. The data collection technique used in this research is library research. The method used is "content analysis" (content analysis). The results of this study indicate that the concept of nusyuz in Article 84 of the KHI when viewed through a textual approach from two different schools of thought, it is the opinion of the Shafi'i school that is more appropriate or relevant to the concept of nusyuz in the KHI than the opinion of the Hanafi school. This is due to the influence of the thought pattern of Islamic law enforcement in Indonesia which is based on the Syafi'i school, as can be seen from the process of compiling the Compilation of Islamic Law through the book path in which most of the fiqh books are of the Shafi'i school of thought.